1994
DOI: 10.1152/ajprenal.1994.267.5.f758
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nitrobenzylthioninosine-sensitive adenosine uptake by cultured kidney cells

Abstract: The effect of nitrobenzylthioinosine (NBTI) on [3H]adenosine uptake and the characterization of the [3H]NBTI binding in cell (primary cultures and LLC-PK1 cell line) plasma membrane and brush-border membrane (BBM) vesicles from pig renal cortices and LLC-PK1 cells was analyzed. [3H]adenosine uptake was strongly inhibited by NBTI in nonconfluent cells, whereas it was totally insensitive to the reagent in BBM. The concentration dependence of [3H]adenosine uptake in BBM was linear, suggesting simple diffusion. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These data suggest that intestinal CNT1 may be regulated by substrate availability [141]. Studies in pig kidney LLC-PK1 cells showed that treatment with chlorophenyl adenosine 3',5'-cyclic monophosphate reduced es activity and NBMPR binding sites in the cells, and the reduction may involve phosphorylation of the transporter molecule or of a protein that interacts with it [143]. Studies in pig kidney LLC-PK1 cells showed that treatment with chlorophenyl adenosine 3',5'-cyclic monophosphate reduced es activity and NBMPR binding sites in the cells, and the reduction may involve phosphorylation of the transporter molecule or of a protein that interacts with it [143].…”
Section: Other Cell Typesmentioning
confidence: 88%
“…These data suggest that intestinal CNT1 may be regulated by substrate availability [141]. Studies in pig kidney LLC-PK1 cells showed that treatment with chlorophenyl adenosine 3',5'-cyclic monophosphate reduced es activity and NBMPR binding sites in the cells, and the reduction may involve phosphorylation of the transporter molecule or of a protein that interacts with it [143]. Studies in pig kidney LLC-PK1 cells showed that treatment with chlorophenyl adenosine 3',5'-cyclic monophosphate reduced es activity and NBMPR binding sites in the cells, and the reduction may involve phosphorylation of the transporter molecule or of a protein that interacts with it [143].…”
Section: Other Cell Typesmentioning
confidence: 88%
“…Other signal molecules, such as cytokines and pancreatic hormones, modulate nucleoside transport by activating protein kinases. Activation of protein kinase C affects nucleoside transport in chromaffin cells [85] and neuroblastoma cells [86], while protein kinase A inhibits the equilibrative uptake of adenosine in cultured kidney cells [87] and neuroblastoma cells [86]. In human B lymphocytes, tumor necrosis factor‐α activates concentrative transport and decreases equilibrative transport of uridine by activating protein kinase C [88].…”
Section: Pentose Phosphates As a Carbon And An Energy Sourcementioning
confidence: 99%
“…However, in some non-neural es-systems and Na + -dependent processes the regulation by phosphorylation/dephosphorylation seems to present some variability [Lee, 1994;Sayós et al, 1994;Coe et al, 1996;Soler et al, 1998]. Furthermore, the non-neural es-transporter of microvascular endothelial cells from the adrenal medulla was not regulated to any extent by protein kinases A and C [Sen et al, 1996], indicating that not all the es-sytems are susceptible to regulation by the same kind of mechanisms.…”
Section: Regulatory Studies Of Nucleoside Transporters: Allosteric Momentioning
confidence: 99%